Potential‐Energy Surfaces, the Born–Oppenheimer Approximations, and the Franck–Condon Principle: Back to the Roots. Issue 17 (27th June 2016) - Mustroph, Heinz
Abstract: The concept of a potential‐energy surface (PES) is central to our understanding of spectroscopy, photochemistry, and chemical kinetics. However, the terminology used in connection with the basic approximations is variously, and somewhat confusingly, represented with such phrases as "adiabatic", "Born–Oppenheimer", or "Born–Oppenheimer adiabatic" approximation. Concerning the closely relevant and important Franck–Condon principle (FCP), the IUPAC definition differentiates between a classical and quantum mechanical formulation. Consequently, in many publications we find terms such as "Franck–Condon (excited) state", or a vertical transition to the "Franck–Condon point" with the "Franck–Condon geometry" that relaxes to the excited‐state equilibrium geometry. The Born–Oppenheimer approximation and the "classical" model of the Franck–Condon principle are typical examples of misused terms and lax interpretations of the original theories. In this essay, we revisit the original publications of pioneers of the PES concept and the FCP to help stimulate a lively discussion and clearer thinking around these important concepts. Abstract : Potential‐energy surfaces (PES) : The terms "Born–Oppenheimer", "Born–Oppenheimer adiabatic approximation", and the "classical" model of the Franck–Condon principle are typical examples of misused and lax interpretations of the original theories. The original publications of pioneers of the PES concept and the Franck–Condon principle are revisited to help stimulate a lively discussion and clearer thinking around these important concepts.